A genome-wide RNA interference screen identifies a differential role of the Mediator CDK8 module subunits for GATA/ RUNX-activated transcription in Drosophila - Gobert, Vanessa; Osman, Dani; Bras, Stéphanie; Augé, Benoit; Boube, Muriel; Bourbon, Henri-Marc; Horn, Thomas; Boutros, Michael; Haenlin, Marc; Waltzer, Lucas (Molecular and cellular biology, 2010)
Transcription factors of the RUNX and GATA families play key roles in the control of cell fate choice and differentiation, notably in the hematopoietic system. During Drosophila hematopoiesis, the RUNX factor Lozenge and the GATA factor Serpent cooperate to induce crystal cell differentiation. We used Serpent/Lozenge-activated transcription as a paradigm to identify modulators of GATA/RUNX activity by a genome-wide RNA interference screen in cultured Drosophila blood cells. Among the 129 factors identified, several belong to the Mediator complex. Mediator is organized in three modules plus a regulatory “CDK8 module,” composed of Med12, Med13, CycC, and Cdk8, which has long been thought to behave as a single functional entity. Interestingly, our data demonstrate that Med12 and Med13 but not CycC or Cdk8 are essential for Serpent/Lozenge-induced transactivation in cell culture. Furthermore, our in vivo analysis of crystal cell development show that, while the four CDK8 module subunits control the emergence and the proliferation of this lineage, only Med12 and Med13 regulate its differentiation. We thus propose that Med12/Med13 acts as a coactivator for Serpent/Lozenge during crystal cell differentiation independently of CycC/Cdk8. More generally, we suggest that the set of conserved factors identified herein may regulate GATA/RUNX activity in mammals.